Iraq Crude Oil Exports – October, November, December/ 2015 - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2016)
Table 1.Iraq Crude Oil Exports – October 2015 ......................................................... 1 Table 2.Iraq Crude Oil Exports – November 2015 ...................................................... 2 Table 3.Iraq Crude Oil Exports – December 2015 ...................................................... 3 Table 4. Gas production Activities , Types of Oils and Asphalt for October 2015 . 4 Table 5. Production and Types of Oils and Asphalt for November 2015 ............... 5 Table 6. Production and Types of Oils and Asphalt for December 2015 .......... 6 Table 7. crude oil production rates and crude discharge for November / 2015 ........ 7 Table 8. Oil Production Rates for November /2015 ..................................................... 7 Table 9. crude oil production rates and crude discharge for December / 2015 ........ 8 Table 10. Oil Production Rates for December /2015 ………….………….……………………….8